2010
DOI: 10.1039/b914709h
|View full text |Cite
|
Sign up to set email alerts
|

Ionogel-based light-actuated valves for controlling liquid flow in micro-fluidic manifolds

Abstract: We present the fabrication, characterisation and performance of four novel ionic liquid polymer gels (ionogels) as photo-actuated valves incorporated into microfluidic manifolds. The ionogels incorporate benzospiropyran units and phosphonium based ionic liquids. Each ionogel is photo-polymerised in-situ in the channels of a poly(methyl methacrylate) micro-fluidic device, generating a manifold incorporating four different micro-valves. The valves are actuated by simply applying localised white light irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 38 publications
1
106
0
Order By: Relevance
“…[13] It is well known that lower crosslinking density results in increased water uptake, however this can result in a weaker mechanical stable gel. Therefore a compromise between physical-mechanical integrity (high degree of crosslinking) and extent of actuation (low degree of crosslinking) was established for this ionogel material in our previous publications.…”
Section: E) Reversible Swelling-shrinking Behaviourmentioning
confidence: 99%
“…[13] It is well known that lower crosslinking density results in increased water uptake, however this can result in a weaker mechanical stable gel. Therefore a compromise between physical-mechanical integrity (high degree of crosslinking) and extent of actuation (low degree of crosslinking) was established for this ionogel material in our previous publications.…”
Section: E) Reversible Swelling-shrinking Behaviourmentioning
confidence: 99%
“…18 The %H of all the photopolymerised microstructures was measured after 30 min (Figure 3b, Figure 4) of white light irradiation following the same protocol described above. In all cases, the [P 6,6,6,14 ][NTf 2 ] microstructures exhibit the greatest %H reduction, followed by [P 6,6,6,14 ][dca] and [P 6,6,6,14 ][Cl].…”
Section: Shrinking Rates Of Ionogel Microstructuresmentioning
confidence: 99%
“…15 We have recently published several papers on phosphonium-based ILs, and their use in ionogels. 16,17,18 In this paper, we report the synthesis of photoresponsive poly(Nisopropylacrylamide) ionogels functionalised with spiropyran chromophores, and examine their ability to be photopatterned into complex microstructures using a performance is determined by the swelling and shrinking behaviour, and therefore it is one of the basic properties that needs to be considered if it is to form the basis of a useful polymer actuator. 8 Due to the large surface-area-to-volume ratio of the photopatterned microstructures compared to bulk macro scaled gel structures, the rates of water diffusion into and out of the gel are highly accelerated.…”
mentioning
confidence: 99%
“…1 This ability makes LCEs attractive candidates for a variety of applications in robotics, photonics, and microfluidics. It has been demonstrated that modified LCEs can exhibit thermal, 2-5 electrical, 6 and photo-induced 7,8 actuation; based on these achievements, a number of devices such as microvalves, 9 optical tweezers, and microgrippers 10 among others have been reported. Photo-induced actuation in particular is attractive because it can be triggered by an external "remote" stimulus (rather than by direct heating, which is inconvenient for most practical applications) and because the speed and periodicity of the stimulus can be finely controlled.…”
mentioning
confidence: 99%